Introduction to ChatGPT and OpenAI. (Packt Publishing, 2023)
OpenAI ChatGPT is a powerful language model that uses advanced ML techniques to generate human-like text responses. With a vast knowledge base and the ability to understand and respond to a wide range of topics, ChatGPT provides detailed and insightful answers, making it a valuable tool for applications such as customer support, content creation, and virtual assistance. Its NLP capabilities and conversational skills make it versatile for text-based interactions. The course begins with an introduction to OpenAI ChatGPT and explains its technology and features/use cases. We will set up an OpenAI account. We will explore how to write a speech and create a PowerPoint presentation and resume. We will write computer programs and debug using ChatGPT. We will build a machine learning model using ChatGPT and "word cloud" using Streamlit. We will create a blog post summary, hashtags, and suggest titles for YouTube videos. We will examine VLookUp in Excel and analyze the net promoter score (NPS). We will explore 10 cool applications of ChatGPT. We will explore DALL-E and Whisper AI and look at other alternatives to ChatGPT. We will independently use ChatGPT to create summaries, speeches, lesson plans, and resumes upon completion. We will develop programs, debug them with ChatGPT, and use other OpenAI platforms such as Whisper and DALL-E. What You Will Learn Understand the technology behind OpenAI and ChatGPT Examine the features, use cases, risks, and limitations of ChatGPT Discover how ChatGPT can be used to improve one's productivity Create a computer program and debug errors using ChatGPT Learn to use other OpenAI platforms such as Whisper and DALL-E Create speeches, translate text, and subject lesson plans using ChatGPT Audience This course is a beginner-level course into the world of OpenAI ChatGPT, DALL-E, and Whisper AI, where you explore the basic concepts. This course caters to students, teachers, AI enthusiasts, and anyone who uses Google but wants to know more about ChatGPT and its capabilities. The course does not have specific prerequisites, but prior programming and machine learning knowledge would be desirable. About The Author Seaport AI: Trainer Govind Kumar has over 2 decades of experience managing Technology, Operations and Quality in top MNCs & startups. Held leadership roles (including Founder & CEO of an AI & Automation Startup) and managed businesses across Asia Pacific & Japan region. He has expertise in AI, Six Sigma and Innovation He successfully incubated Centers of Excellence for fraud prevention and service analytics. Has significant experience in design thinking based product development and management. Played a critical role in developing products for emerging markets. Education & Certification B. Tech and Full time MBA from top institutes in India Certifications in six sigma and project management. Accolades Won global awards in the areas of Customer Experience, Leadership Excellence, Quality and Technology. Featured in the cover of CIO Review Magazine. Board of Studies Member of the Board of Studies at Loyola College, Chennai, India (a 96 year old institution).